Modified hollow cadmium sulfide photocatalytic reducing agent as well as preparation method and application thereof

Through the preparation of modified hollow cadmium sulfide photocatalyst, the problem of difficult degradation of methyl orange pollution in the existing technology is solved, and efficient, economical and rapid wastewater treatment effect is achieved, which is suitable for treating high-concentration methyl orange wastewater.

CN120662381APending Publication Date: 2025-09-19ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510823770.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-19
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Existing technologies are difficult to effectively degrade methyl orange pollution. The chemical oxidation method is complex to operate and has high energy consumption. The pure phase CdS photogenerated carrier recombination rate is high and photocorrosion is serious. The physical and biological treatment efficiency is low, making it difficult to achieve efficient and economical wastewater treatment.

Method used

By preparing a modified hollow cadmium sulfide photocatalytic reducing agent, silica microspheres are reacted with sodium citrate, cadmium chloride, ammonia water and thiourea solution to form nano hollow cadmium sulfide, which is further etched in sodium hydroxide solution and treated in 1-octadecene to introduce functional groups, forming a stable surface modification layer and enhancing the photocatalytic performance.

Benefits of technology

High-concentration methyl orange wastewater can be efficiently degraded under visible light conditions, the stability and adsorption capacity of the photocatalyst are improved, the separation and transfer of photogenerated electrons and holes are significantly enhanced, and economical and rapid wastewater treatment is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120662381A_ABST
    Figure CN120662381A_ABST
Patent Text Reader

Abstract

The invention discloses a modified hollow cadmium sulfide photocatalytic reducing agent and a preparation method and application thereof, and belongs to the technical field of wastewater treatment.The preparation method comprises the steps that silicon dioxide microspheres and deionized water are mixed to prepare suspension liquid, a sodium citrate aqueous solution, a cadmium chloride aqueous solution, ammonia water and a thiourea aqueous solution are added into the suspension liquid, the mixture is stirred to be uniform and then heated for a reaction, and the modified hollow cadmium sulfide photocatalytic reducing agent is obtained; preparing to obtain a silicon dioxide and cadmium sulfide composite material; immersing the silicon dioxide and cadmium sulfide composite material into a sodium hydroxide solution, heating and etching to obtain nano hollow cadmium sulfide; the preparation method comprises the following steps: immersing nano hollow cadmium sulfide into a 1-octadecene solution, carrying out heating reaction, and carrying out alcohol washing and drying to obtain the modified hollow cadmium sulfide photocatalytic reducing agent. The modified hollow cadmium sulfide composite photocatalyst is synthesized through a silicon dioxide template method and a thermal decomposition method, and high-concentration methyl orange industrial wastewater can be efficiently degraded under the condition of visible light irradiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment, and particularly relates to a modified hollow cadmium sulfide photocatalytic reducing agent and a preparation method and application thereof. Background Art

[0002] Methyl orange, a typical azo dye, is widely used in textile printing and dyeing, leather processing, and biomedical dyeing. Its molecular structure, composed of azo groups, sulfonic acid groups, and a conjugated aromatic ring system, is highly chemically stable. Studies have shown that methyl orange can persist in natural water bodies for long periods, not only causing color pollution but also producing highly toxic metabolites such as aniline, which pose a serious threat to ecosystems and human health.

[0003] Currently, the main methods for treating printing and dyeing wastewater include physical methods, chemical oxidation methods, and biodegradation methods. Physical and biological methods, however, cannot fundamentally address the problem of methyl orange contamination, and struggle to effectively decolorize and reduce solution toxicity. While physical methods can adsorb some organic pollutants, the regeneration and disposal costs of the adsorbents are high. Biological treatment technologies, however, are limited by the chemical stability and biotoxicity of methyl orange, resulting in low degradation efficiency, long treatment times, and difficulty meeting emission standards. While chemical oxidation methods can efficiently and environmentally degrade methyl orange, they suffer from complex operations, high energy consumption, and high costs.

[0004] Photocatalytic technology involves photocatalysts absorbing energy from sunlight, exciting electrons in the valence band to transition to the conduction band, forming electron-hole pairs with strong redox capabilities that redox pollutants. This technology offers advantages such as environmental friendliness and low cost. Cadmium sulfide, however, has a smaller band gap and can be excited by visible light. However, pure CdS suffers from inherent drawbacks such as a high recombination rate of photogenerated carriers and severe photocorrosion, limiting its practical application. Constructing hollow structures through morphology manipulation can not only effectively increase specific surface area and active site exposure, but also extend the optical path, increase light absorption, and inhibit photocorrosion. Modification can introduce functional groups that serve as transport pathways for electron-hole pairs, reducing photogenerated carrier recombination and enhancing catalyst stability, but also serve as active sites to promote the adsorption and degradation of organic pollutants. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a modified hollow cadmium sulfide photocatalytic reducing agent and its preparation method and application to solve the problems mentioned in the background technology or achieve better technical effects.

[0006] In order to solve the above technical problems, the inventors have arrived at the technical solution of the present invention through practice and summary. The present invention discloses a method for preparing a modified hollow cadmium sulfide photocatalytic reducing agent, comprising mixing silica microspheres with deionized water to prepare a suspension, adding a sodium citrate aqueous solution, a cadmium chloride aqueous solution, ammonia water and a thiourea aqueous solution to the suspension, stirring evenly and then heating to react, thereby preparing a silica-cadmium sulfide composite material; immersing the silica-cadmium sulfide composite material in a sodium hydroxide solution, heating and etching to obtain nano-hollow cadmium sulfide; immersing the nano-hollow cadmium sulfide in a 1-octadecene solution, heating to react, and then washing with alcohol and drying to obtain a modified hollow cadmium sulfide photocatalytic reducing agent.

[0007] Furthermore, the mass ratio of the silica microspheres to the volume of deionized water is 3 mg:2 mL.

[0008] Furthermore, the preparation method of the silica microspheres is: adding tetraethyl orthosilicate dropwise to a uniform solution formed by ammonia water and anhydrous ethanol, stirring at room temperature for 1 hour, washing the precipitate several times with deionized water and ethanol, and drying; the volume ratio of the ammonia water to anhydrous ethanol is 2 to 3:9, the volume ratio of the tetraethyl orthosilicate to the uniform solution is 1 to 2:35, the stirring rate is 600 r / min, and the drying temperature is 40 to 60°C.

[0009] Furthermore, the mass fraction of the ammonia water is 29%, the concentrations of the sodium citrate aqueous solution, the cadmium chloride aqueous solution and the thiourea aqueous solution are all 1 mol / L; and the volume ratio of the sodium citrate solution, the cadmium chloride solution, the ammonia water and the thiourea solution is 2:1:4:4.

[0010] Furthermore, the concentration of the sodium hydroxide solution is 1 mol / L, and the volume ratio of the mass of the silicon dioxide cadmium sulfide composite material to the sodium hydroxide solution is 2-3 mg:1 mL.

[0011] Furthermore, the temperature of the temperature-raising etching is 90° C., and the time is 3 to 5 hours; the process of the temperature-raising reaction is: heating to 150° C., stirring to remove moisture, then heating to 190 to 210° C., and reacting for 0.5 to 1 hour.

[0012] Furthermore, the volume ratio of the mass of the nano hollow cadmium sulfide to the 1-octadecene solution is 43 mg:10-30 mL.

[0013] Furthermore, the preparation method of any of the above-mentioned modified hollow cadmium sulfide photocatalytic reducing agents comprises the following steps:

[0014] (1) Tetraethyl orthosilicate was added dropwise to a uniform solution of ammonia water and anhydrous ethanol, stirred at room temperature for 1 hour, and the precipitate was washed several times with deionized water and ethanol, and dried to obtain silica;

[0015] (2) placing the silicon dioxide obtained in step (1) in an aqueous solution to form a suspension, adding sodium citrate solution, cadmium chloride solution, ammonia water and thiourea solution respectively, stirring evenly, heating to 80° C. to react, obtaining a precipitate, repeatedly washing with deionized water 3 to 5 times, and drying at 40 to 60° C. to obtain a silicon dioxide cadmium sulfide composite material;

[0016] (3) immersing the silicon dioxide cadmium sulfide composite material obtained in step (2) in a sodium hydroxide solution and etching for 4 hours, and the obtained precipitate is repeatedly rinsed with deionized water until the pH is neutral, and dried to obtain nano hollow cadmium sulfide;

[0017] (4) The nano hollow cadmium sulfide obtained in step (3) is placed in an 1-octadecene solution, heated to 150° C., stirred for 40 minutes to remove moisture, then heated to 190-210° C., reacted for 0.5-1 hour, rinsed with ethanol 3-5 times, and dried to obtain a modified hollow cadmium sulfide photocatalytic reducing agent.

[0018] Furthermore, a modified hollow cadmium sulfide photocatalytic reducing agent is prepared by any of the above-mentioned preparation methods.

[0019] Furthermore, the modified hollow cadmium sulfide photocatalytic reducing agent is used in treating water pollution caused by dye molecules and / or heavy metal ions.

[0020] Furthermore, the dye molecules are selected from one or more of methyl orange, methylene blue and rhodamine B; and the heavy metal ions are selected from one or more of hexavalent chromium and pentavalent arsenic.

[0021] Furthermore, the methyl orange concentration is 50-100 mg / L; under the condition of visible light irradiation, the modified hollow cadmium sulfide photocatalytic reducing agent gradually oxidizes and reduces the acidic or neutral methyl orange solution into small molecular substances, and finally mineralizes into carbon dioxide and water.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The present invention synthesizes a modified hollow cadmium sulfide composite photocatalyst by a silica template method and a thermal decomposition method, which can efficiently degrade high-concentration methyl orange industrial wastewater under visible light irradiation.

[0024] (2) Both the internal and external surfaces of the hollow structure of the modified hollow cadmium sulfide composite photocatalyst prepared by the present invention can serve as reaction active sites, and the specific surface area is significantly increased, which can adsorb more dye molecules and photocatalytic intermediates, thereby improving the adsorption-photocatalytic efficiency. The hollow structure can also effectively absorb and scatter light, thereby prolonging the residence time of light in the catalyst. In addition, the hollow structure can also provide more interfaces and channels, which are conducive to the rapid separation and transfer of photogenerated electrons and holes, reduce recombination, and improve the photocatalytic efficiency.

[0025] (3) The present invention performs oxygen modification on hollow cadmium sulfide, which not only introduces functional groups but also improves the stability of the material. The modified hollow cadmium sulfide composite material successfully introduces a large number of C=C. Among them, there may be some uncoordinated cadmium atoms or sulfur atoms on the surface of the hollow cadmium sulfide. Active sites such as 1-octadecene can undergo electrophilic addition or coordination with the active sites on the surface of cadmium sulfide through its double bond or terminal methyl, such as sulfide bond (-SC-). This coordination can enhance the adsorption stability of organic compounds on the surface of hollow cadmium sulfide, thereby forming a stable surface modification layer. These functional groups can not only adsorb and degrade pollutant molecules and highly toxic intermediates, prolong the service life of the photocatalyst, but also participate in charge transfer as electron donors or acceptors.

[0026] (4) The cadmium sulfide of the present invention can provide electron-hole pairs under visible light conditions, so the material has more excellent photocatalytic properties and stability. Through synergistic effects, it can degrade high-concentration methyl orange industrial wastewater in a short time. This can achieve economical, effective, rapid, and harmless treatment of high-concentration methyl orange wastewater.

[0027] (5) The material of the present invention exhibits a series of excellent properties for photocatalytic degradation of methyl orange wastewater: high photocatalytic activity, good reproducibility, low energy consumption, and environmental friendliness. Furthermore, it has a simple production process and mild preparation conditions, making it an ideal choice for treating high-concentration methyl orange industrial wastewater. Its advantages of simple operation, low cost, and high efficiency are fully demonstrated in the actual treatment process. The properties of photocatalytic reduction can also be extended to the treatment of wastewater contaminated by other dye molecules and heavy metal ions, such as methylene blue, rhodamine B, hexavalent chromium, and pentavalent arsenic. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The following is a technical roadmap for synthesizing the modified hollow cadmium sulfide photocatalytic reducing agent of the present invention;

[0029] Figure 2Surface scanning electron microscope images of the modified hollow cadmium sulfide photocatalytic reducing agent in Example 2 of the present invention; wherein, (1) is a SEM image of the hollow cadmium sulfide (magnified 50,000 times); (2) is a SEM image of the modified hollow cadmium sulfide at a magnification of 50,000 times; (3) is a SEM image of the modified hollow cadmium sulfide at a magnification of 200,000 times; (4) is a SEM image of the modified hollow cadmium sulfide after photocatalytic degradation of methyl orange (magnified 50,000 times);

[0030] Figure 3 This is a transmission electron microscope image of the modified hollow cadmium sulfide photocatalytic reducing agent in Example 2 of the present invention;

[0031] Figure 4 The N2 adsorption-desorption isotherms and pore size distributions of the modified hollow cadmium sulfide photocatalytic reducing agent before and after modification in Example 2 of the present invention are shown; wherein, (1) is the N2 adsorption-desorption isotherms of silica cadmium sulfide, hollow cadmium sulfide, and modified hollow cadmium sulfide; (2) is the BJH pore size distribution of the three materials;

[0032] Figure 5 The ultraviolet diffuse reflectance spectrum of the modified hollow cadmium sulfide photocatalytic reducing agent in Example 2 of the present invention is shown in FIG. 1 , wherein (1) is the absorbance of the hollow cadmium sulfide and the modified hollow cadmium sulfide in different light wavelength ranges; and (2) is the band gap width of the hollow cadmium sulfide and the modified hollow cadmium sulfide. DETAILED DESCRIPTION

[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0034] Unless otherwise specified, the raw materials or reagents used in the following examples and comparative examples are commercially available products or products prepared by conventional techniques. All reagents used were purchased from Shanghai Titan Technology Co., Ltd.

[0035] The mass percentage of the ammonia water used in the present invention is 29% (w / w), and Single Metal is less than 50 ppt.

[0036] A method for preparing a modified hollow cadmium sulfide photocatalytic reducing agent comprises the following steps:

[0037] (1) Ammonia water and anhydrous ethanol are firstly prepared into a uniform solution at a volume ratio of 2 to 3:9, and then tetraethyl orthosilicate is added dropwise at a volume ratio of 1 to 2:35 to the uniform solution. After stirring at a speed of 600 r / min at room temperature for 1 hour, the precipitate is washed several times with deionized water and ethanol, and dried at 40 to 60°C to obtain silica microspheres;

[0038] (2) mixing the silica microspheres obtained in step (1) with deionized water in a mass-to-volume ratio of 3:2 to form a suspension; first adding sodium citrate solution to the suspension and continuously stirring for 10 minutes, then adding cadmium chloride solution and continuously stirring for 20 minutes, and finally adding ammonia water and thiourea solution dropwise, stirring evenly, heating to 80°C, reacting for 2-4 hours, obtaining a precipitate, repeatedly washing with deionized water for 3-5 times, and drying at 40-60°C to obtain a silica-cadmium sulfide composite material; wherein the concentrations of the sodium citrate solution, cadmium chloride solution and thiourea solution are all 1 mol / L, and the volume ratios of the added sodium citrate solution, cadmium chloride solution, ammonia water and thiourea solution are 2:1:4:4;

[0039] (3) immersing the silica cadmium sulfide composite material obtained in step (2) in a 1 mol / L sodium hydroxide solution according to a mass volume ratio of 2 to 3 mg: 1 mL for etching for 3 to 5 hours, and after precipitation is complete, repeatedly rinsing with deionized water until the pH is neutral, and drying to obtain nano hollow cadmium sulfide;

[0040] (4) adding the nano hollow cadmium sulfide obtained in step (3) to the 1-octadecene solution in a mass volume ratio of 43 mg: 10-30 mL, heating to 150° C., removing water after stirring, heating again to 190-210° C., reacting for 0.5-1 h, then washing with ethanol 3-5 times, and drying at 40-60° C. to obtain a modified hollow cadmium sulfide photocatalytic reducing agent, such as Figure 1 shown.

[0041] Example 1

[0042] A method for preparing a modified hollow cadmium sulfide photocatalytic reducing agent, the preparation steps are as follows:

[0043] S1: Add 24 mL of ammonia water to 81 mL of anhydrous ethanol and stir to form a homogeneous solution. Then, add 4.2 mL of tetraethyl orthosilicate dropwise. After stirring at room temperature for 1 h, centrifuge to obtain a precipitate. Wash with deionized water and ethanol several times, and dry at 60°C to obtain silica microspheres.

[0044] S2: Weigh 300 mg of the silica microspheres obtained in step S1 and place them in 200 mL of deionized water to form a suspension. Add 2 mL of a 1 mol / L sodium citrate aqueous solution to the suspension and continue stirring for 10 minutes. Then, add 1 mL of a 1 mol / L cadmium chloride aqueous solution dropwise and continue stirring for 20 minutes. Then, slowly add 4 mL of ammonia water and 4 mL of a 1 mol / L thiourea aqueous solution in sequence. After stirring evenly, heat to 80°C and react for 3 hours to obtain a precipitate. Rinse repeatedly with deionized water 3 to 5 times and dry to obtain a silica-cadmium sulfide composite material.

[0045] S3: Weigh 120 mg of the silica-cadmium sulfide composite material obtained in step S2 and immerse it in 50 mL of 1 mol / L sodium hydroxide solution. Heat the solution to 90° C. and etch for 4 h. The resulting precipitate is repeatedly rinsed with deionized water until the pH is neutral, and dried to obtain nano-hollow cadmium sulfide.

[0046] S4: Weigh 86 mg of the nano-hollow cadmium sulfide obtained in step S3 and immerse it in 20 mL of 1-octadecene solution, raise the temperature to 150° C., stir for 40 minutes to remove moisture, then raise the temperature to 200° C., react for 35 minutes, rinse with ethanol 3 to 5 times, and dry to obtain a modified hollow cadmium sulfide photocatalytic reducing agent.

[0047] Example 2

[0048] A method for preparing a modified hollow cadmium sulfide photocatalytic reducing agent, the preparation steps are as follows:

[0049] S1: Add 24 mL of ammonia water to 81 mL of anhydrous ethanol and stir to form a homogeneous solution. Then, add 4.2 mL of tetraethyl orthosilicate dropwise. After stirring at room temperature for 1 h, centrifuge to obtain a precipitate. Wash with deionized water and ethanol several times, and dry at 60°C to obtain silica microspheres.

[0050] S2: Weigh 300 mg of the silica microspheres obtained in step S1 and place them in 200 mL of deionized water to form a suspension. Add 2 mL of a 1 mol / L sodium citrate aqueous solution to the suspension and continue stirring for 10 minutes. Then, add 1 mL of a 1 mol / L cadmium chloride aqueous solution dropwise and continue stirring for 20 minutes. Then, slowly add 4 mL of ammonia water and 4 mL of a 1 mol / L thiourea aqueous solution in sequence. After stirring evenly, heat to 80°C and react for 3 hours to obtain a precipitate. Rinse repeatedly with deionized water 3 to 5 times and dry to obtain a silica-cadmium sulfide composite material.

[0051] S3: Weigh 120 mg of the silica-cadmium sulfide composite material obtained in step S2 and immerse it in 50 mL of 1 mol / L sodium hydroxide solution. Heat the solution to 90° C. and etch for 4 h. The resulting precipitate is repeatedly rinsed with deionized water until the pH is neutral, and dried to obtain nano-hollow cadmium sulfide.

[0052] S4: Weigh 86 mg of the nano-hollow cadmium sulfide obtained in step S3 and immerse it in 40 mL of 1-octadecene solution, raise the temperature to 150° C., stir for 40 minutes to remove moisture, then raise the temperature to 200° C., react for 35 minutes, rinse with ethanol 3 to 5 times, and dry to obtain a modified hollow cadmium sulfide photocatalytic reducing agent.

[0053] Example 3

[0054] A method for preparing a modified hollow cadmium sulfide photocatalytic reducing agent, the preparation steps are as follows:

[0055] S1: Add 24 mL of ammonia water to 81 mL of anhydrous ethanol and stir to form a homogeneous solution. Then, add 4.2 mL of tetraethyl orthosilicate dropwise. After stirring at room temperature for 1 h, centrifuge to obtain a precipitate. Wash with deionized water and ethanol several times, and dry at 60°C to obtain silica microspheres.

[0056] S2: Weigh 300 mg of the silica microspheres obtained in step S1 and place them in 200 mL of deionized water to form a suspension. Add 2 mL of a 1 mol / L sodium citrate aqueous solution to the suspension and continue stirring for 10 minutes. Then, add 1 mL of a 1 mol / L cadmium chloride aqueous solution dropwise and continue stirring for 20 minutes. Then, slowly add 4 mL of ammonia water and 4 mL of a 1 mol / L thiourea aqueous solution in sequence. After stirring evenly, heat to 80°C and react for 3 hours to obtain a precipitate. Rinse repeatedly with deionized water 3 to 5 times and dry to obtain a silica-cadmium sulfide composite material.

[0057] S3: Weigh 120 mg of the silica-cadmium sulfide composite material obtained in step S2 and immerse it in 50 mL of 1 mol / L sodium hydroxide solution. Heat the solution to 90° C. and etch for 4 h. The resulting precipitate is repeatedly rinsed with deionized water until the pH is neutral, and dried to obtain nano-hollow cadmium sulfide.

[0058] S4: Weigh 86 mg of the nano-hollow cadmium sulfide obtained in step S3 and immerse it in 60 mL of 1-octadecene solution, raise the temperature to 150° C., stir for 40 minutes to remove moisture, then raise the temperature to 200° C., react for 35 minutes, rinse with ethanol 3 to 5 times, and dry to obtain a modified hollow cadmium sulfide photocatalytic reducing agent.

[0059] Adsorption test: Prepare two different methyl orange standard solutions with pH values ​​of 1 and 7, with a concentration of 100 mg / L. Take 100 mg of each of the three catalysts prepared above and place them in 100 mL of methyl orange solutions with different pH values. Let them stand for adsorption for 12 hours in the dark. The methyl orange concentrations in the solutions after adsorption are shown in Table 1 below:

[0060] Table 1 Concentration of methyl orange in the solution after adsorption of different catalysts prepared in Examples 1 to 3

[0061]

[0062] Table 1 shows that the modified hollow cadmium sulfide photocatalytic reducing agents prepared with three different formulations all exhibited superior methyl orange removal capabilities at pH 1 compared to those at pH 7. This is because under acidic conditions, the cadmium sulfide surface carries a positive charge, generating strong electrostatic attraction with the methyl orange anion, allowing it to adsorb more methyl orange molecules, providing a continuous supply of pollutants for photocatalysis and reducing the recombination of electron-hole pairs. Furthermore, under acidic conditions, the azo structure in the methyl orange molecule transforms into a quinone structure, weakening the azo bond energy and making it more susceptible to free radical attack and cleavage. This comparison shows that Example 2 exhibits the best methyl orange removal capability. Therefore, Example 2 was selected as the optimal preparation scheme.

[0063] Photocatalytic test: Prepare a methyl orange standard solution with a pH of 1 and a concentration of 50 mg / L. Take 100 mg of each of the three catalysts prepared above and place them in the methyl orange standard solution with a volume of 100 mL. Irradiate with visible light at 450 nm (irradiance of 171 mW / cm 2 ) was used for photocatalytic reduction, and samples were taken every 5 minutes to measure the methyl orange concentration. The test results are shown in Table 2 below:

[0064] Table 2 Residual methyl orange concentration in the solution after photocatalytic test of different catalysts prepared in Examples 1 to 3

[0065] Time (min) Example 1 Example 2 Example 3 5 37.6 22.0 29.4 10 24.8 10.5 18.6 15 19.7 4.3 12.1 20 8.2 0.0 7.1 25 7.3 0.0 4.8 30 6.0 0.0 3.8

[0066] Table 2 shows that the results of photocatalytic reduction tests conducted on the photocatalysts prepared in different Examples indicate that the modified hollow cadmium sulfide photocatalytic reducing agent prepared in Example 2 can essentially completely remove 50 mg / L of methyl orange within 30 minutes. Furthermore, Example 2 exhibits significantly greater adsorption-catalytic reduction capabilities for methyl orange than Examples 1 and 3.

[0067] Comparative test: a methyl orange standard solution with a pH of 1 and a concentration of 100 mg / L was prepared. 100 mg of the modified hollow cadmium sulfide photocatalytic reducing agent prepared in Example 2 was placed in 100 mL of the methyl orange standard solution. The reaction mixture was placed in the dark and under 450 nm visible light (irradiance of 171 mW / cm 2 ) under the conditions of dark conditions and visible light conditions, respectively, samples were taken every 1 hour and 10 minutes to detect the concentration of methyl orange. The test results are shown in Table 3 below:

[0068] Table 3 Residual methyl orange concentration in the solution after testing in dark and visible light conditions in Example 2

[0069]

[0070]

[0071] As shown in Table 3, the modified hollow cadmium sulfide photocatalytic reducing agent of Example 2 of the present invention takes 6 hours to remove 60% of methyl orange in the solution under dark conditions, while it takes 6 hours under 450nm visible light irradiation (irradiance of 171mW / cm 2 ) under the conditions of only 20 minutes, and after 50 minutes, the methyl orange in the solution was completely removed. This comparison shows that the efficiency of methyl orange removal increased by about 18 times under the conditions of adding visible light.

[0072] Photocatalytic test: Two different methyl orange standard solutions with pH values ​​of 1 and 7 were prepared at a concentration of 50 mg / L. The modified hollow cadmium sulfide photocatalytic reducing agent prepared in Example 2 was selected. The experiment was carried out under light illumination conditions with wavelengths of 365 nm, 380 nm, 400 nm, 420 nm, 450 nm, 480 nm, 500 nm, and 550 nm, respectively. After 30 minutes, samples were taken to detect the concentration of methyl orange. The test results are shown in Table 4 below:

[0073] Table 4 Residual methyl orange concentration in the solution of the modified hollow cadmium sulfide photocatalytic reducing agent prepared in Example 2 after testing under different wavelength light conditions

[0074] Light source wavelength / nm pH = 1, methyl orange mg / L pH = 7, methyl orange mg / L 365 13.5 20.4 380 12.4 17.6 400 9.8 13.1 420 5.6 11.3 450 0 8.3 480 9.2 12.9 500 10.9 15.5 550 17.7 24.8

[0075] As shown in Table 4, the efficiency of the modified hollow cadmium sulfide photocatalytic reducing agent in methyl orange solutions at pH 1 and 7 increases first and then decreases as the wavelength of the irradiated light increases from 365 nm to 550 nm, and the degradation rate is highest when the wavelength of the irradiated light is 450 nm. This comparison shows that the modified hollow cadmium sulfide photocatalytic reducing agent of the present invention can better degrade high-concentration methyl orange wastewater when the wavelength of visible light is between 420 and 480 nm.

[0076] Cyclic test: a methyl orange standard solution with a pH of 1 and a concentration of 50 mg / L was prepared, 100 mg of the modified hollow cadmium sulfide photocatalytic reducing agent prepared in Example 2 was placed in 100 mL of the methyl orange standard solution, and the photocatalytic reduction agent was irradiated under 450 nm visible light (irradiance of 171 mW / cm 2 ) irradiation conditions, sampling every 10 minutes to test the concentration of methyl orange. After 30 minutes of reaction, the photocatalyst was separated by filtration, then washed several times with deionized water and ethanol, and dried at 40-60°C. The dried catalyst was redispersed in a new methyl orange standard solution and the next photocatalytic cycle test was carried out. The test results are shown in Table 5 below:

[0077] Table 5 Residual methyl orange concentration in the solution of the modified hollow cadmium sulfide photocatalytic reducing agent prepared in Example 2 after several cycles of photocatalytic testing

[0078] Number of cycles 10min, methyl orange mg / L 20min, methyl orange mg / L 30min, methyl orange mg / L 1 15.0 4.0 0 2 15.2 4.6 0 3 15.6 5.1 0 4 16.1 5.7 0.4 5 16.8 6.3 0.8 6 17.4 6.6 1.3 7 17.9 7.2 1.6 8 18.3 7.7 2.1 9 18.8 8.1 2.6 10 19.5 8.9 3.0

[0079] Table 5 shows that after 10 cycles of photocatalytic degradation of methyl orange wastewater, the modified hollow cadmium sulfide photocatalytic reducing agent prepared by the present invention exhibited only a 6% decrease in degradation rate compared to the initial photocatalytic degradation of methyl orange wastewater. This demonstrates that the catalytic reducing agent prepared by the present invention exhibits excellent stability and cyclic performance, maintaining high catalytic degradation performance even after multiple cycles at high concentrations of methyl orange.

[0080] Detection and analysis: The modified hollow cadmium sulfide photocatalytic reducing agent prepared in Example 2 of the present invention was analyzed by SEM and TEM respectively. Figure 2 and Figure 3 As shown in the figure, the modified hollow CdS photocatalytic reducing agents all showed a spherical morphology with complete CdS shell, similar size, and high monodispersity, without obvious agglomeration. Figure 2 (4) It can be seen that the morphology of the photocatalyst before and after the photocatalytic reaction remains basically consistent, and no large-scale breakage occurs, indicating that the catalyst has good stability.

[0081] The silicon dioxide cadmium sulfide composite material prepared in Example 2 and the hollow cadmium sulfide photocatalytic reducing agent before and after modification were ground into powders, and their surface areas were measured respectively. The results are as follows: Figure 4 As shown. Figure 4 (1) It can be seen that the adsorption capacity of the silica-cadmium sulfide composite material is the lowest. The adsorption capacity of the hollow cadmium sulfide before and after modification is higher, and it has a larger specific surface area. The specific surface area of ​​the hollow cadmium sulfide after modification becomes smaller because the chemical modification causes the partial pore structure to collapse. Figure 4 (2) It can be seen that the pore size distribution of the modified hollow cadmium sulfide is between that of the silica cadmium sulfide composite material and the hollow cadmium sulfide, and the average pore size is the largest.

[0082] The hollow cadmium sulfide photocatalytic reducing agent prepared in Example 2 was ground into powder, and its absorption characteristics to light of different wavelengths were analyzed. The results are as follows: Figure 5 As shown by Figure 5 (1) The hollow cadmium sulfide before and after modification has a high absorption peak in the wavelength range of 380-500nm, and the absorbance drops sharply around 520nm. The absorption curve of the modified hollow cadmium sulfide is higher than that of the hollow cadmium sulfide, indicating that the modified hollow cadmium sulfide has better photocatalytic activity; Figure 5 (2) Analysis shows that the modified hollow cadmium sulfide has a smaller band gap of 2.20 eV, indicating that the material has a wider light absorption range, generates more photogenerated carriers, and can participate in photocatalytic redox reactions more effectively.

[0083] This invention synthesizes a modified hollow cadmium sulfide composite photocatalyst using a silica template method and thermal decomposition methods. It can efficiently degrade high-concentration methyl orange industrial wastewater under visible light irradiation. Both the internal and external surfaces of the hollow structure of this material serve as reactive sites, significantly increasing the specific surface area and absorbing more dye molecules and photocatalytic intermediates, thereby improving the adsorption-photocatalytic efficiency. The hollow structure also effectively absorbs and scatters light, extending the residence time of light in the catalyst. Furthermore, the hollow structure provides more interfaces and channels, facilitating the rapid separation and transfer of photogenerated electrons and holes, reducing recombination and improving photocatalytic efficiency. Oxygen modification of hollow cadmium sulfide not only introduces functional groups but also improves the material's stability. The modified hollow cadmium sulfide composite material successfully incorporates a large number of C=C atoms. The hollow cadmium sulfide surface may contain some active sites, such as uncoordinated cadmium atoms or sulfur atoms. 1-Octadecene, through its double bonds or terminal methyl groups, can undergo electrophilic addition or coordination with these active sites on the cadmium sulfide surface, such as thioether bonds (-SC-). This coordination enhances the adsorption stability of organic compounds on the hollow cadmium sulfide surface, thereby forming a stable surface modification layer. These functional groups not only adsorb and degrade pollutant molecules and highly toxic intermediates, extending the life of the photocatalyst, but also act as electron donors or acceptors in charge transfer. Cadmium sulfide can donate electron and hole pairs under visible light, resulting in the material's superior photocatalytic properties and stability. This synergistic effect allows for the rapid degradation of high-concentration methyl orange industrial wastewater in a short time. This approach enables the economical, efficient, rapid, and harmless treatment of high-concentration methyl orange wastewater.

[0084] The modified hollow cadmium sulfide photocatalytic reductant prepared by this invention exhibits a series of excellent properties for the photocatalytic degradation of methyl orange wastewater, including high photocatalytic activity, good reproducibility, low energy consumption, and environmental friendliness. Furthermore, its simple production process and mild preparation conditions make it an ideal choice for treating high-concentration methyl orange industrial wastewater. Its advantages of ease of operation, low cost, and high efficiency have been fully demonstrated in actual treatment processes. The photocatalytic reduction properties can also be extended to the treatment of wastewater contaminated by other dye molecules and heavy metal ions, such as methylene blue, rhodamine B, hexavalent chromium, and pentavalent arsenic.

[0085] Photocatalytic degradation of Cr (VI) test: a Cr (VI) standard solution with a pH of 1 and a concentration of 50 mg / L was prepared. 100 mg of the modified hollow cadmium sulfide photocatalytic reducing agent prepared in Example 2 was placed in 100 mL of the Cr (VI) standard solution and irradiated with 450 nm visible light (irradiance of 171 mW / cm 2 The experiment was conducted under the conditions of , and samples were taken every 5 minutes to detect the concentration of Cr(VI). The test results are shown in Table 6 below:

[0086] Table 6 Photocatalytic Cr(VI) activity of the modified hollow cadmium sulfide photocatalytic reducing agent prepared in Example 2

[0087] Time / min Cr(VI)mg / L 0 50 5 22.6 10 14.2 15 9.1 20 4.8 25 1.5 30 0

[0088] As shown in Table 6, the modified hollow cadmium sulfide photocatalytic reducing agent prepared by the present invention photocatalytically reduces Cr(VI) under 450nm light conditions, with a degradation rate of 100% within 30 minutes. After absorbing light energy, the modified hollow cadmium sulfide transfers free electrons in the valence band to the conduction band through functional groups, generating electron-hole pairs. These electron-hole pairs are captured by Cr(VI) adsorbed on the surface of the composite material, thereby accelerating the reduction reaction of Cr(VI) to Cr(III). The reduced Cr(III) ions are ultimately released into the solution through electrostatic repulsion, regenerating adsorption sites for further removal of Cr(VI).

[0089] Simultaneous photocatalytic removal of Cr(VI) and methyl orange in binary solution: 100 mL of a mixed solution containing 50 mg / L methyl orange and 50 mg / L Cr(VI) was prepared. 100 mg of the modified hollow cadmium sulfide photocatalytic reducing agent prepared in Example 2 was placed in the mixed solution and irradiated with 450 nm visible light (irradiance of 171 mW / cm 2 The experiment was conducted under the conditions of , and samples were taken every 5 minutes to detect the concentrations of Cr (VI) and methyl orange. The test results are shown in Table 7 below:

[0090] Table 7 Simultaneous photocatalytic removal of methyl orange and Cr(VI) by the modified hollow cadmium sulfide photocatalytic reducing agent prepared in Example 2 in binary solution

[0091] Time / min Methyl orange mg / L Hexavalent chromium mg / L 0 50 49.7 5 20.6 18.1 10 11.7 8.9 15 4.5 1.6 20 1.1 0 25 0 0 30 0 0

[0092] The results showed that under 450nm visible light irradiation (irradiance of 171mW / cm 2 ) under the conditions of 100 nm (100 nm) and 100 nm (200 nm), Cr(VI) and methyl orange were completely removed within 25 and 20 minutes, respectively. The removal efficiency of both pollutants was higher than that obtained from single-pollutant solutions. This phenomenon is primarily due to the fact that in the binary coexistence system, the light source excites the modified hollow cadmium sulfide to produce a large number of electron-hole pairs. The rapid adsorption and reduction of Cr(VI) consumes a large number of free electrons, preventing the recombination of electron-hole pairs. As a result, more oxidative active substances can participate in the photocatalytic degradation of methyl orange, enhancing the photocatalytic performance.

[0093] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations that come within the meaning and range of equivalents of the claims be embraced therein.

[0094] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

Claims

1. A method for preparing a modified hollow cadmium sulfide photocatalytic reducing agent, characterized in that: Silica microspheres are mixed with deionized water to prepare a suspension, sodium citrate aqueous solution, cadmium chloride aqueous solution, ammonia water and thiourea aqueous solution are added to the suspension, stirred evenly and then heated to react to prepare a silica-cadmium sulfide composite material; the silica-cadmium sulfide composite material is immersed in a sodium hydroxide solution, and etched at a high temperature to obtain nano hollow cadmium sulfide; the nano hollow cadmium sulfide is immersed in a 1-octadecene solution, heated to react, and then washed with alcohol and dried to obtain a modified hollow cadmium sulfide photocatalytic reducing agent.

2. The method for preparing the modified hollow cadmium sulfide photocatalytic reducing agent according to claim 1, characterized in that: The mass ratio of the silica microspheres to the volume of deionized water is 3 mg:2 mL.

3. The method for preparing the modified hollow cadmium sulfide photocatalytic reducing agent according to claim 2, characterized in that: The preparation method of the silica microspheres comprises: adding tetraethyl orthosilicate dropwise to a uniform solution formed by ammonia water and anhydrous ethanol, stirring at room temperature for 1 hour, washing the precipitate several times with deionized water and ethanol, and drying; the volume ratio of the ammonia water to the anhydrous ethanol is 2 to 3:9, the volume ratio of the tetraethyl orthosilicate to the uniform solution is 1 to 2:35, the stirring rate is 600 r / min, and the drying temperature is 40 to 60°C.

4. The method for preparing the modified hollow cadmium sulfide photocatalytic reducing agent according to claim 1, characterized in that: The mass fraction of the ammonia water is 29%, the concentrations of the sodium citrate aqueous solution, the cadmium chloride aqueous solution and the thiourea aqueous solution are all 1 mol / L; and the volume ratio of the sodium citrate solution, the cadmium chloride solution, the ammonia water and the thiourea solution is 2:1:4:

4.

5. The method for preparing the modified hollow cadmium sulfide photocatalytic reducing agent according to claim 1, characterized in that: The concentration of the sodium hydroxide solution is 1 mol / L, and the volume ratio of the mass of the silicon dioxide cadmium sulfide composite material to the sodium hydroxide solution is 2-3 mg:1 mL.

6. The method for preparing the modified hollow cadmium sulfide photocatalytic reducing agent according to claim 1, characterized in that: The temperature of the temperature-raising etching is 90° C., and the time is 3 to 5 hours. The process of the temperature-raising reaction is: heating to 150° C., stirring to remove moisture, then heating to 190 to 210° C., and reacting for 0.5 to 1 hour.

7. The method for preparing the modified hollow cadmium sulfide photocatalytic reducing agent according to claim 1, characterized in that: The volume ratio of the mass of the nano hollow cadmium sulfide to the 1-octadecene solution is 43 mg:10-30 mL.

8. The method for preparing the modified hollow cadmium sulfide photocatalytic reducing agent according to any one of claims 1 to 7, characterized in that: Here are the steps: (1) Tetraethyl orthosilicate was added dropwise to a uniform solution of ammonia water and anhydrous ethanol, stirred at room temperature for 1 hour, and the precipitate was washed several times with deionized water and ethanol, and dried to obtain silica; (2) placing the silicon dioxide obtained in step (1) in an aqueous solution to form a suspension, adding sodium citrate solution, cadmium chloride solution, ammonia water and thiourea solution respectively, stirring evenly, heating to 80° C. to react, obtaining a precipitate, repeatedly washing with deionized water 3 to 5 times, and drying at 40 to 60° C. to obtain a silicon dioxide cadmium sulfide composite material; (3) immersing the silicon dioxide cadmium sulfide composite material obtained in step (2) in a sodium hydroxide solution and etching for 4 hours, and the obtained precipitate is repeatedly rinsed with deionized water until the pH is neutral, and dried to obtain nano hollow cadmium sulfide; (4) The nano hollow cadmium sulfide obtained in step (3) is placed in an 1-octadecene solution, heated to 150° C., stirred for 40 minutes to remove moisture, then heated to 190-210° C., reacted for 0.5-1 hour, rinsed with ethanol 3-5 times, and dried to obtain a modified hollow cadmium sulfide photocatalytic reducing agent.

9. A modified hollow cadmium sulfide photocatalytic reducing agent, prepared by the preparation method according to any one of claims 1 to 7.

10. Use of the modified hollow cadmium sulfide photocatalytic reducing agent according to claim 9 in treating water pollution caused by dye molecules and / or heavy metal ions.

11. The use according to claim 10, characterized in that The dye molecules are selected from one or more of methyl orange, methylene blue and rhodamine B; the heavy metal ions are selected from one or more of hexavalent chromium and pentavalent arsenic.

12. The use according to claim 11, characterized in that The concentration of methyl orange is 50-100 mg / L; under the condition of visible light irradiation, the modified hollow cadmium sulfide photocatalytic reducing agent gradually oxidizes and reduces the acidic or neutral methyl orange solution into small molecular substances, and finally mineralizes into carbon dioxide and water.

Citation Information

Cited By

  • Preparation method and application of hollow sphere cadmium sulfide / flower-like bismuth tungstate composite photocatalyst

    CN121314700A